2014
DOI: 10.1021/cm404026k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Performance of Synthetic Tetrahedrites

Abstract: Electrical and thermal transport properties of synthetic tetrahedrites Cu10TM2Sb4S13 (TM = Mn, Fe, Co, Ni, Zn) and the solid solution Cu12–x Mn x Sb4S13 (0 ≤ x ≤ 2) have been studied in the context of thermoelectric performance. Among these materials, the parent compound Cu12Sb4S13 exhibits the highest power factor, which is primarily derived from a high electrical conductivity. All substituted derivatives display a significant and uniform reduction in thermal conductivity. Within the TM series, the Mn-substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
187
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(238 citation statements)
references
References 29 publications
17
187
12
Order By: Relevance
“…For Tr = Ni, high ZT value at ∼700 K and good thermal stability up to 783 K were confirmed by other research groups, [49][50][51] whereas for Tr = Ni and Zn (co-doped), ZT = 1 has not been followed up so far. Good figures of merit have been demonstrated also for Tr = Mn, 37,52,53 and Tr = Co, 54,55 as well as samples made of mixed natural and synthetic tetrahedrites. 13,[56][57][58] It should be noted that the natural minerals showed rather low ZT's due to excessive ρ.…”
Section: Tetrahedrite (P-type)mentioning
confidence: 82%
“…For Tr = Ni, high ZT value at ∼700 K and good thermal stability up to 783 K were confirmed by other research groups, [49][50][51] whereas for Tr = Ni and Zn (co-doped), ZT = 1 has not been followed up so far. Good figures of merit have been demonstrated also for Tr = Mn, 37,52,53 and Tr = Co, 54,55 as well as samples made of mixed natural and synthetic tetrahedrites. 13,[56][57][58] It should be noted that the natural minerals showed rather low ZT's due to excessive ρ.…”
Section: Tetrahedrite (P-type)mentioning
confidence: 82%
“…3a, Cu 2 Se possesses two sublattices: the rigid FCC framework of Se atoms and the disordered and flowing sublattice of Cu. At high temperatures, Cu ions migrate from one site (interstitial one formed by Se) to another, exhibiting a flowing character that is Figure 1 Timeline of zT for selected Cu-based superionic conductors [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (red), tetragonal [28][29][30][31][32][33][34][35][36][37] (blue) and distorted [38][39][40][41][42][43][44][45][46][47][48][49] (green) diamond-like materials and BiCuSeO oxyselenides (purple) [50][51][52][53][54][55][56][57][58][59]…”
Section: Decoupled Transport Properties By Two Independent Sublatticesmentioning
confidence: 99%
“…Such a concept has been successfully explored to study cage compounds with oversized atomic cages (∼>10 atoms) such as clathrates and partially filled skutterudites. 2 Recently, crystalline materials based on Cu 12 Sb 4 S 13 tetrahedrites containing earth-abundant and environmental friendly elements were found to possess lattice thermal conductivities below 1 W m −1 K −1 from 300 to 700 K. [3][4][5][6] Such a low lattice thermal conductivity, combined with their favorable electrical properties, yields high figure-of-merit values in these tetrahedrites. Various experimental and computational studies have found that this low lattice thermal conductivity is accompanied by anomalous atomic dynamics in tetrahedrites.…”
mentioning
confidence: 99%